Genetic screening for hypertension and COVID-19 reveals functional variation of SPEG potentially associated with severe COVID-19 in women - Luo, Yu-Si; Shen, Xiang-Chun; Li, Wei; Wu, Guo-Feng; Yang, Xiao-Meng; Guo, Ming-Yang; Chen, Fang; Shen, Hu-Yan; Zhang, Ping-Ping; Gao, Han; Nie, Ying; Wu, Jia-Hong; et al. (Frontiers in Genetics, 2023)
The coronavirus disease 2019 (COVID-19) pandemic, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has led to more than 6.4 million deaths worldwide. The prevalent comorbidity between hypertension and severe COVID-19 suggests common genetic factors may affect the outcome of both diseases. As both hypertension and severe COVID-19 demonstrate sex-biased prevalence, common genetic factors between the two diseases may display sex-biased differential associations. By evaluating COVID-19 association signals of 172-candidate hypertension single nucleotide polymorphisms (SNPs) derived from more than one million European individuals in two sex-stratified severe COVID-19 genome-wide association studies from UK BioBank with European ancestry, we revealed one functional cis expression quantitative trait locus of SPEG (rs12474050) showing sex-biased association with severe COVID-19 in women. The risk allele rs12474050*T associates with higher blood pressure. In our study, we found it is significantly correlated with lower SPEG expression in muscle-skeletal but with higher expression in both brain cerebellum and cerebellar hemisphere. Additionally, nominal significances were detected for the association between rs12474050*T and lower SPEG expression in both heart left ventricle and atrial appendage; among these tissues, the SPEG expression is nominally significantly higher in females than in males. Further analysis revealed SPEG is mainly expressed in cardiomyocytes in heart and is upregulated upon SARS-CoV-2 infection, with significantly higher upregulation of SPEG only observed in female but not in male COVID-19 patients compared to both normal female and male individuals, suggesting upregulation of SPEG is a female-specific protective mechanism against COVID-19 induced heart damage. Taken together, our analyses suggest the involvement of SPEG in both hypertension and severe COVID-19 in women, which provides new insights for sex-biased effect of severe COVID-19 in women.